P-cadherin functional role is dependent on E-cadherin cellular context: a proof of concept using the breast cancer model - Ribeiro, Ana Sofia (2018)
P-cadherin overexpression is associated with worse breast cancer survival, being a poor prognostic marker as well as a putative therapeutic target for the aggressive triple-negative and basal-like carcinomas (TNBCs). Previously, we have shown that P-cadherin promotes breast cancer invasion of cells where membrane E-cadherin was maintained; however, it suppresses invasion in models without endogenous cadherins, like melanomas. Here, we investigated if P-cadherin expression would interfere with the normal adhesion complex and which were the cellular/molecular consequences, constituting, in this way, a new mechanism by which E-cadherin invasive-suppressor function was disrupted. Using breast TNBC models, we demonstrated, for the first time, that P-cadherin co-localizes with E-cadherin, promoting cell invasion due to the disruption caused in the interaction between E-cadherin and cytoplasmic catenins. P-cadherin also induces cell migration and survival, modifying the expression profile of cells expressing wild-type E-cadherin and contributing to alter their cellular behaviour. Additionally, E- and P-cadherin co-expressing cells significantly enhanced in vivo tumour growth, compared with cells expressing only E- or only P-cadherin. Finally, we still found that co-expression of both molecules was significantly correlated with high-grade breast carcinomas, biologically aggressive, and with poor patient survival, being a strong prognostic factor in this disease. Our results show a role for E- and P-cadherin co-expression in breast cancer progression and highlight the potential benefit of targeting P-cadherin in the aggressive tumours expressing high levels of this protein.